P594Role of autophagy in chloramphenicol-induced cardioprotection. (15th July 2014) - Koncsos, G; Giricz, Z; Gorbe, A; Gottlieb, RA; Ferdinandy, P
Abstract: Purpose: We have shown previously that chloramphenicol (CAP) reduces infarct size, although its mechanism is not fully understood. It has also been evidenced that autophagy plays important role in cardioprotection. Therefore, our aim was to investigate whether autophagy is necessary for CAP-induced cardioprotection. Methods: Neonatal rat cardiomyocytes were isolated and treated for 1h as follows: (1) 300 μM CAP, (2) 10 μM chloroquine (CQ), (3) 300 μM CAP and 10 μM CQ, and (4) non-treated control. After the indicated treatments markers of autophagy were determined by Western blots. In ex vivo experiments isolated rat hearts were perfused with Krebs-Henseleit buffer containing 300 μM CAP initiated 15 min before the onset of 30 min global ischemia and 120 min of reperfusion. To inhibit early phases of autophagy, a group of CAP-treated hearts was perfused with 200 nM recombinant Tat-Atg5K130R protein (inhibiting autophagosome formation) before CAP administration. To investigate the role of lysosomal degradation in CAP-induced cardioprotection another group of isolated hearts was perfused with 5 μM CQ (inhibiting lysosomal degradation) before CAP administration. TTC staining was performed to determine infarct size in all groups. Results: CAP induces autophagy in neonatal cardiomyocytes by increasing the level of LC3-II and decreasing the phosphorylation of p70S6K. CAP significantly reduced infarct size in ex vivo perfused hearts, while inhibition of autophagosome formation (by Tat-Atg5K130R protein) was abolished CAP-induced cardioprotection. However, the inhibition of lysosomal degradation (by CQ) did not influence CAP -induced cardioprotection. Conclusions: Here we evidenced an induced autophagy and a downregulation in the mTOR pathway due to CAP treatment in cardiomyocytes. Our results demonstrate that formation of autophagosomes is essential for the cardioprotective effect of CAP, while it is unaffected by a block in the clearance of autophago-lysosomes. These results suggest that inducers of autophagy may form the basis of future cardioprotective therapies.